The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.22435/asp.v10i2.206
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Dataran Tinggi dan Dataran Rendah terhadap Keberagaman Spesies Anopheles spp. di Provinsi Nusa Tenggara Timur

Abstract: Ecological studies on the vector species diversity usually focused on particular habitats and not a comparative study. Therefore, a research has been carried out to see the variation from one of many aspects which affects the condition of a habitat such as altitude. This study aimed to determine the Anopheles spp. species diversity between highland and lowland captured in the research of Vektora 2015 This study is a further analysis of Vektora Research Data from 2015 to 2016 in East Nusa Tenggara Province. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
(9 reference statements)
0
4
0
4
Order By: Relevance
“…14 Study conducted by Widawati in East Nusa Tenggara had found that Anopheles annularis is the most commonly Anopheles found in the lowlands whereas Anopheles vagus is the most commonly Anopheles found in the highlands of East Nusa Tenggara Province. 15 The environmental conditions are different for each endemic area and it becomes locally unique for local governments to intervene in dealing with malaria. A study conducted in Nunukan Regency, East Kalimantan, found that the presence of livestock near home had a p-value of 0.217, which did not have a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…14 Study conducted by Widawati in East Nusa Tenggara had found that Anopheles annularis is the most commonly Anopheles found in the lowlands whereas Anopheles vagus is the most commonly Anopheles found in the highlands of East Nusa Tenggara Province. 15 The environmental conditions are different for each endemic area and it becomes locally unique for local governments to intervene in dealing with malaria. A study conducted in Nunukan Regency, East Kalimantan, found that the presence of livestock near home had a p-value of 0.217, which did not have a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini dilakukan pada daerah dataran tinggi, Dataran tinggi/pegunungan merupakan bagian permukaan bumi yang mendatar dan terletak pada ketinggian lebih dari 600 m di atas permukaan laut. 8 Banjar Lumbuan, Desa Sulahan, Kecamatan Susut, Kabupaten Bangli merupakan desa yang berada di Kabupaten Bangli yang secara geografis desa ini terletak 1.219 m diatas permukaan laut. Desa ini memiliki iklim tropis dengan suhu udara relatif rendah berkisar antara 15 0 C -30 0 C. Jumlah penduduk di desa Lumbuan adalah 847 jiwa dan jumlah lansia di desa Lumbuan sekitar 184 orang.…”
Section: Metodeunclassified
“…Hal yang sama terdapat pada penelitian Abolla et al, (2018) yang mengemukakan bahwa elevasi atau ketinggian tempat merupakan penentu keberhasilan pembangunan pertanian karena memiliki hubungan dengan suhu serta kelembaban udara, dimana semakin tinggi tempat pertanian maka suhunya akan menurun dan kelembaban akan meningkat. Menurut Widawati et al, (2018) area dataran tinggi terletak pada ketinggian 600meter diatas permukaan laut. Sedangkan menurut Supriastuti, (2021) dataran tinggi merupakan dataran yang terletak pada area ketinggian diatas 700meter diatas permukaan laut.…”
Section: Pertanianunclassified